Origin and significance of macroscopic organic aggregates from the lacustrine Aptian Crato Konservat-Lagerstätte - Varejão, Filipe Giovanini; Warren, Lucas Veríssimo [UNESP]; Rodrigues, Mariza Gomes [UNESP]; Assine, Mario Luis [UNESP]; Simões, Marcello Guimarães [UNESP] (Elsevier, 2024)
The Crato Konservat-Lagerstätte is one of the main Mesozoic fossil sites from Gondwana, recording a wide diversity of terrestrial and non-marine aquatic fossils of great paleobiological and evolutionary significance. This conservation deposit is recorded in a 9 m-thick interval of laminite, microbialite, and grainstone deposited in a lake system with variable water level, alternating moments of hypersaline and freshwater conditions. Despite numerous studies describing new species of plants, arthropods, fish, pterosaurs, birds, and many others, there remains a significant gap in our understanding of the most common and archetypal fossils, which are the rod-shaped macrofossils found on bedding surfaces in distinct stratigraphic intervals of the Crato Konservat-Lagerstätte. The rod-shaped macrofossils are up to 1.6 cm-long and 0.1 cm-wide, straight to curved compressions that preserve pyritized microfossils. Here we interpret the rod-shaped macrofossils as macroscopic organic aggregates that sank into the lakebed in a process called lake snow. During high organic productivity periods in the epilimnion, planktonic organisms thrived and produced exopolymers responsible for aggregation. Their concentrations in the limestone bedding planes reflect intensity of lake snow and environmental seasonality. Aggregates are prolate particles that are commonly oriented, suggesting their transport as bedload for short distances, which was facilitated by biostabilization by microbes and their exopolymers. Finally, pyritization was mediated by microbial communities living in the lakebed.
Keywords: Exceptional preservation; Lake snow; Macroscopic aggregates; Microbial process; Plankton